Development of STREAM-ETHNO-Based Learning Media for Elementary School Students: Pengembangan Media Pembelajaran Berbasis STREAM-ETHNO untuk Siswa Sekolah Dasar - Sri Setiawaty; Riska Imanda; Karismayani; Wandira Kinanti; Nur Dhihila AT (LPPM Universitas Malikussaleh, 2024)
The need for virtual media aligns with the Ministry of Education and Culture program. The fulfillment of ICT-based learning facilities, including the need for facilities in learning, must be balanced with the availability of virtual learning media where students and teachers need to be given facilities and support to use and develop learning media according to their needs. Professional teachers not only need to prepare lesson materials but are also required to be creative in using learning approaches and developing learning media. Learning media will facilitate interaction between teachers and students, making learning activities more effective and efficient. This is the main reason researchers integrate STREAM learning based on Aceh's local wisdom in teaching media in the form of learning media using educational software. This study aims to determine the quality of STREAM-Etno learning media. To achieve this goal, this study was designed using a design model based on the ADDIE model for the development stage due to the researcher's limited time. The research stages include preliminary analysis to understand the needs and facilities in implementing virtual technology and learning media development design. Based on the results of the research and development that has been carried out, the STREAM-Etno integrated learning media can be declared valid and feasible, so it is suitable for use in grade III elementary school students, based on the results of expert assessment validation obtained an average percentage of 92.6% in the material aspect and 95% in the media aspect with the category